Multilayer electronic component

By setting a high-content silver coating between the outer electrode strips of the multi-layer ceramic capacitor, the problem of prone to bending cracks under external bending stress of ceramic capacitors is solved, and a higher bending stress absorption capacity and capacitor stability are achieved.

JP2025037803APending Publication Date: 2025-03-18SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024125156
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-06
Filing Date
2024-07-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing multi-layer ceramic capacitors are prone to bending cracks under external bending stress, and it is difficult to effectively absorb or eliminate stresses that cause ceramic body to rupture.

Method used

A silver (Ag) coating structure is used to form a silver coating between the ribbon portions of the external electrode, and an average atomic percentage of the silver coating reaches 90% or more, and a silver coating is provided between the electrode layer and the conductive resin layer to improve the bending stress absorption capacity of the capacitor.

Benefits of technology

By causing the peeling of the external electrode, the bending cracks in the multi-layer ceramic capacitors under bending stress are effectively suppressed, and the bending stress tolerance of the capacitor is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037803000001_ABST
    Figure 2025037803000001_ABST
Patent Text Reader

Abstract

To provide a multilayer electronic component suppressing warpage stress applied from the outside.SOLUTION: A multilayer electronic component includes: a body 110 which includes dielectric layers 111, and internal electrodes 121, 122, and comprises a first surface and a second surface facing each other in a first direction, a third surface and a fourth surface connected to the first surface, and the second surface, and facing each other in a second direction, and a fifth surface and a sixth surface connected to the first surface to the fourth surface, and facing each other in a third direction; and external electrodes 131, 132 including a connection portion disposed on the third surface and the fourth surface, and a band portion extending from the connection portion to a portion of the first surface and second surface. Therein, the external electrodes include: an electrode layer 131a, 132a connected to the internal electrodes and including a first conductive metal and glass; a conductive resin layer 131c, 132c disposed on the electrode layer and including a second conductive metal and a resin; and a silver coating layer 131b, 132b which is disposed between an electrode layer and a conductive resin layer of the band portion, and has an average thickness between 2 μm and 5 μm.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multilayer electronic component. [Background technology]

[0002] Multilayer ceramic capacitors (MLCCs), which are one type of multilayer electronic component, are chip-type capacitors that are mounted on printed circuit boards of various electronic products such as visual devices such as liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smartphones, and mobile phones, and serve to charge and discharge electricity.

[0003] Such multilayer ceramic capacitors have the advantages of being small yet high capacitance and easy to mount, and can be used as components of various electronic devices. As various electronic devices such as computers and mobile devices become smaller and have higher output, there is an increasing demand for multilayer ceramic capacitors to be smaller and have higher capacitance.

[0004] However, when an external impact is applied to a ceramic body, the ceramic body has a tendency to break without undergoing plastic deformation, and therefore a structure capable of absorbing or eliminating the tensile stress transmitted to the ceramic body is required to prevent bending cracks.

[0005] Therefore, a method is being used in which a resin-based electrode is added to the external electrode structure to prevent external bending stress from being transmitted to the ceramic body, but research is being conducted on various structural designs and materials to further improve bending strength. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 2018-098475 [Patent Document 2] Korean Patent Publication No. 10-2019-0116177 Summary of the Invention [Problem to be solved by the invention]

[0007] One of the problems to be solved by the present invention is to provide a multilayer electronic component having improved bending stress.

[0008] One of the problems that the present invention aims to solve is to suppress the occurrence of bending cracks in a multilayer electronic component by inducing peel-off in an external electrode when an external bending stress is applied.

[0009] However, some of the problems that the present invention aims to solve are not limited to the above-mentioned contents, and can be more easily understood in the course of describing specific embodiments of the present invention. [Means for solving the problem]

[0010] A multilayer electronic component according to an embodiment of the present invention includes a main body including dielectric layers and internal electrodes alternately arranged with the dielectric layers in a first direction, the main body including first and second surfaces facing each other in the first direction, third and fourth surfaces connected to the first and second surfaces and facing each other in a second direction, and fifth and sixth surfaces connected to the first to fourth surfaces and facing each other in the third direction, and an external electrode including connection portions arranged on the third and fourth surfaces, and a band portion extending from the connection portions to parts of the first and second surfaces, the external electrode including an electrode layer connected to the internal electrodes and including a first conductive metal and glass, a conductive resin layer arranged on the electrode layer and including a second conductive metal and resin, and a silver (Ag) coating layer arranged between the electrode layer and the conductive resin layer of the band portion, and an average thickness of the silver (Ag) coating layer may be 2 μm or more and 5 μm or less.

[0011] A multilayer electronic component according to another embodiment of the present invention includes a main body including dielectric layers and internal electrodes alternately arranged with the dielectric layers in a first direction, the main body including first and second surfaces facing each other in the first direction, third and fourth surfaces connected to the first and second surfaces and facing each other in a second direction, and fifth and sixth surfaces connected to the first to fourth surfaces and facing each other in the third direction, and an external electrode including connection portions arranged on the third and fourth surfaces, and a band portion extending from the connection portions to parts of the first and second surfaces, the external electrode including an electrode layer connected to the internal electrodes and including a first conductive metal and glass, a conductive resin layer arranged on the electrode layer and including a second conductive metal and resin, and a silver (Ag) coating layer arranged between the electrode layer and the conductive resin layer of the band portion, and the silver (Ag) coating layer may have an average atomic percentage of silver (Ag) of 90 at % or more. Effect of the Invention

[0012] One of the advantages of the present invention is that the bending stress of a multilayer electronic component is improved.

[0013] One of the advantages of the present invention is that when an external bending stress is applied, peel-off is induced in the external electrodes, thereby suppressing the occurrence of bending cracks in the multilayer electronic component.

[0014] However, the various and beneficial advantages and effects of the present invention are not limited to the above, and can be more easily understood in the course of describing specific embodiments of the present invention. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic perspective view of a multilayer electronic component according to an embodiment of the present invention; [Diagram 2] FIG. 2 is a schematic exploded perspective view showing a laminated structure of internal electrodes. [Diagram 3] 2 is a schematic cross-sectional view taken along line II' of FIG. 1. [Figure 4]2 is a schematic cross-sectional view taken along line II-II' in FIG. 1. [Diagram 5] 4 is a schematic diagram showing an enlarged view of region M in FIG. 3. [Figure 6] 1 is an image taken by SEM of a region of an external electrode according to an embodiment of the present invention. [Figure 7] (a) to (d) are images of copper (Cu), silver (Ag), nickel (Ni), and tin (Sn) in a region of Figure 6 analyzed in EDS mode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, the embodiments of the present invention will be described with reference to specific embodiments and the accompanying drawings. However, the embodiments of the present invention can be modified into various other forms, and the scope of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those skilled in the art. Therefore, the shape and size of elements in the drawings may be exaggerated for clearer explanation, and elements indicated by the same reference numerals in the drawings are the same elements.

[0017] In order to clearly explain the present invention in the drawings, parts that are not relevant to the explanation are omitted, and the size and thickness of each component shown in the drawings are arbitrarily shown for convenience of explanation, so the present invention is not necessarily limited to those shown in the drawings. Components having the same function within the same concept will be described using the same reference numerals. Furthermore, throughout the specification, when a part is said to "include" a certain component, this does not mean that other components are excluded, but that the part may further include other components, unless otherwise specified.

[0018] In the drawings, the first direction can be defined as the stacking direction or thickness T direction, the second direction can be defined as the length L direction, and the third direction can be defined as the width W direction.

[0019] Multilayer Electronic Components FIG. 1 is a schematic perspective view of a multilayer electronic component according to one embodiment of the present invention, FIG. 2 is a schematic separated perspective view showing the multilayer structure of internal electrodes, FIG. 3 is a schematic cross-sectional view taken along line I-I' in FIG. 1, FIG. 4 is a schematic cross-sectional view taken along line II-II' in FIG. 1, and FIG. 5 is a schematic enlarged view of region M in FIG. 3.

[0020] A multilayer electronic component according to an embodiment of the present invention will be described in detail below with reference to Figures 1 to 5. Although a multilayer ceramic capacitor will be described as an example of a multilayer electronic component, the present invention can also be applied to various electronic products that use a dielectric composition, such as inductors, piezoelectric elements, varistors, thermistors, and the like.

[0021] A multilayer electronic component 100 according to an embodiment of the present invention includes a dielectric layer 111 and internal electrodes 121, 122 arranged alternately with the dielectric layer 111 in a first direction, a main body 110 including first and second surfaces 1, 2 facing each other in the first direction, third and fourth surfaces 3, 4 connected to the first and second surfaces 1, 2 and facing each other in the second direction, and fifth and sixth surfaces 5, 6 connected to the first to fourth surfaces 1, 2, 3, 4 and facing each other in the third direction, connection portions arranged on the third and fourth surfaces 3, 4, and connecting portions extending from the connection portions to parts of the first and second surfaces 1, 2. and external electrodes 131, 132 including a band portion connected to the internal electrodes 121, 122, the external electrodes 131, 132 including electrode layers 131a, 132a including a first conductive metal and glass, conductive resin layers 131c, 132c disposed on the electrode layers 131a, 132a and including a second conductive metal and resin, and silver (Ag) coating layers 131b, 132b disposed between the electrode layers and the conductive resin layers of the band portion, the average thickness of the silver (Ag) coating layers 131b, 132b may be 2 μm or more and 5 μm or less.

[0022] The body 110 may be formed by alternately stacking dielectric layers 111 and internal electrodes 121, 122.

[0023] More specifically, the body 110 may include a capacitance forming portion Ac that is disposed inside the body 110 and includes first internal electrodes 121 and second internal electrodes 122 that are alternately arranged to face each other across the dielectric layer 111 to form a capacitance.

[0024] Although there is no particular limitation on the specific shape of the body 110, as shown in the figure, the body 110 may have a hexahedral shape or a shape similar thereto. Due to shrinkage of ceramic particles contained in the body 110 during the firing process, the body 110 may have a substantially hexahedral shape, although it is not a hexahedral shape with perfectly straight lines.

[0025] The main body 110 may have first and second surfaces 1, 2 facing each other in a first direction, third and fourth surfaces 3, 4 connected to the first and second surfaces 1, 2 and facing each other in the second direction, and fifth and sixth surfaces 5, 6 connected to the first to fourth surfaces 1, 2, 3, 4 and facing each other in the third direction.

[0026] The plurality of dielectric layers 111 forming the body 110 are in a sintered state, and the boundaries between adjacent dielectric layers 111 may be integrated to such an extent that they are difficult to see without using a scanning electron microscope (SEM).

[0027] The raw material for forming the dielectric layer 111 is not limited as long as a sufficient electrostatic capacitance can be obtained. In general, a perovskite (ABO3)-based material can be used, such as a barium titanate-based material, a lead composite perovskite-based material, or a strontium titanate-based material. The barium titanate-based material can include BaTiO3-based ceramic particles, and examples of the ceramic particles include BaTiO3, BaTiO3 partially solid-dissolved with Ca (calcium), Zr (zirconium), etc. 1-x Ca x )TiO3(0 <x<1)、Ba(Ti 1-y Ca y )O3(0 <y<1)、(Ba 1-x Ca x )(Ti 1-y Zry )O3 (0 < x < 1, 0 < y < 1) or Ba(Ti 1-y Zr y )O3 (0 < y < 1), etc.

[0028] Also, various ceramic additives, organic solvents, binders, dispersants, etc. can be added to particles such as barium titanate (BaTiO3) as raw materials for forming the dielectric layer 111 according to the object of the present invention.

[0029] The thickness td of the dielectric layer 111 does not need to be particularly limited.

[0030] However, in order to achieve a higher capacitance of the multilayer electronic component, the thickness of the dielectric layer 111 may be 3.0 μm or less. In order to more easily achieve miniaturization and higher capacitance of the multilayer electronic component, the thickness of the dielectric layer 111 may be 1.0 μm or less, preferably 0.6 μm or less, and more preferably 0.4 μm or less.

[0031] Here, the thickness td of the dielectric layer 111 can mean the thickness td of the dielectric layer 111 disposed between the first and second internal electrodes 121 and 122.

[0032] On the other hand, the thickness td of the dielectric layer 111 can mean the size of the dielectric layer 111 in the first direction. Also, the thickness td of the dielectric layer 111 can mean the average thickness td of the dielectric layer 111 and can mean the average size of the dielectric layer 111 in the first direction.

[0033] The average size in the first direction of the dielectric layer 111 may be measured by scanning an image of a cross-section of the body 110 in the first and second directions using a scanning electron microscope (SEM) with a magnification of 10,000. More specifically, the average size in the first direction of one dielectric layer 111 may mean an average value calculated by measuring the size in the first direction of one dielectric layer 111 at 30 points equally spaced in the second direction in the scanned image. The 30 equally spaced points may be designated as the capacitance forming portion Ac. Furthermore, if the measurement of such an average value is extended to 10 dielectric layers 111 and the average value is measured, the average size in the first direction of the dielectric layer 111 may be further generalized.

[0034] The internal electrodes 121 and 122 may be laminated alternately with the dielectric layers 111 .

[0035] The internal electrodes 121, 122 may include a first internal electrode 121 and a second internal electrode 122, and the first and second internal electrodes 121, 122 may be alternately arranged to face each other with the dielectric layer 111 constituting the body 110 interposed therebetween, and may be exposed to third and fourth surfaces 3, 4 of the body, respectively. Here, being exposed to one surface of the body may mean being in contact with one surface of the body.

[0036] More specifically, the first internal electrode 121 may be spaced apart from the fourth surface 4 and exposed through the third surface 3, and the second internal electrode 122 may be spaced apart from the third surface 3 and exposed through the fourth surface 4. A first external electrode 131 may be disposed on the third surface 3 of the body 110 and connected to the first internal electrode 121, and a second external electrode 132 may be disposed on the fourth surface 4 of the body 110 and connected to the second internal electrode 122.

[0037] That is, the first internal electrode 121 may be connected to the first external electrode 131 without being connected to the second external electrode 132, and the second internal electrode 122 may be connected to the second external electrode 132 without being connected to the first external electrode 131. In this case, the first and second internal electrodes 121 and 122 may be electrically isolated from each other by the dielectric layer 111 disposed therebetween.

[0038] Meanwhile, the body 110 may be formed by alternately stacking ceramic green sheets on which the first internal electrodes 121 are printed and ceramic green sheets on which the second internal electrodes 122 are printed, and then firing the stacked ceramic green sheets.

[0039] There is no particular limitation on the material forming the internal electrodes 121 and 122, and any material having excellent electrical conductivity can be used. For example, the internal electrodes 121 and 122 can include one or more of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof.

[0040] The internal electrodes 121 and 122 may be formed by printing a conductive paste for internal electrodes, which contains at least one of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof, on a ceramic green sheet. The method for printing the conductive paste for internal electrodes may be a screen printing method or a gravure printing method, but the present invention is not limited thereto.

[0041] On the other hand, the thickness te of the internal electrodes 121 and 122 does not need to be particularly limited.

[0042] However, in order to achieve a high capacity of the multilayer electronic component, the thickness of the internal electrodes 121, 122 may be 1.5 μm or less, or 1.0 μm or less, and in order to more easily achieve a small size and high capacity of the multilayer electronic component, the thickness of the internal electrodes 121, 122 may be 0.6 μm or less, and more preferably 0.4 μm or less.

[0043] Here, the thickness te of the internal electrodes 121 and 122 can mean the size of the internal electrodes 121 and 122 in the first direction. Also, the thickness te of the internal electrodes 121 and 122 can mean the average thickness te of the internal electrodes 121 and 122, and can mean the average size of the internal electrodes 121 and 122 in the first direction.

[0044] The average size of the internal electrodes 121 and 122 in the first direction can be measured by scanning an image of the cross-sections of the main body 110 in the first and second directions with a scanning electron microscope (SEM) at a magnification of 10,000 times. More specifically, the average size of one internal electrode in the first direction can be the average value calculated by measuring the size of one internal electrode in the first direction at 30 equally spaced points in the second direction in the scanned image. The 30 equally spaced points can be specified in the capacitance forming portion Ac. Also, when the measurement of such an average value is extended to 10 internal electrodes to measure the average value, the average size of the internal electrodes in the first direction can be further generalized.

[0045] On the other hand, in one embodiment of the present invention, the average thickness td of at least one of the plurality of dielectric layers 111 and the average thickness te of at least one of the plurality of internal electrodes 121 and 122 can satisfy 2×te < td.

[0046] In other words, the average thickness td of one dielectric layer 111 may be greater than twice the average thickness te of one internal electrode 121 or 122. Preferably, the average thickness td of the plurality of dielectric layers 111 may be greater than twice the average thickness te of the plurality of internal electrodes 121 and 122.

[0047] Generally, for electronic components for high-voltage electrical equipment, the main issue is the reliability problem due to the decrease in the breakdown voltage (BDV) in a high-voltage environment.

[0048] Therefore, in order to prevent a drop in the breakdown voltage in a high-voltage environment, the average thickness td of the dielectric layer 111 is made greater than twice the average thickness te of the internal electrodes 121, 122, thereby increasing the thickness of the dielectric layer, which is the distance between the internal electrodes, and improving the breakdown voltage characteristics.

[0049] If the average thickness td of the dielectric layer 111 is less than twice the average thickness te of the internal electrodes 121, 122, the average thickness of the dielectric layer, which is the distance between the internal electrodes, will be small, and the breakdown voltage may decrease, which may result in a short circuit between the internal electrodes.

[0050] In the high-voltage electronic component, the average thickness te of the internal electrodes may be 1 μm or less, and the average thickness td of the dielectric layers may be 3.0 μm or less, but are not necessarily limited to this.

[0051] Meanwhile, the body 110 may include cover portions 112 and 113 disposed on both end surfaces in the first direction of the capacitance forming portion Ac.

[0052] More specifically, it may include an upper cover part 112 disposed at an upper part of the capacitance forming part Ac in the first direction and a lower cover part 113 disposed at a lower part of the capacitance forming part Ac in the first direction.

[0053] The upper cover part 112 and the lower cover part 113 may be formed by stacking a single dielectric layer 111 or two or more dielectric layers 111 in a first direction on the upper and lower surfaces of the capacitance forming part Ac, respectively, and may basically serve to prevent damage to the internal electrodes 121, 122 due to physical or chemical stress.

[0054] The upper cover part 112 and the lower cover part 113 do not include the internal electrodes 121, 122 and may include the same material as the dielectric layer 111. That is, the upper cover part 112 and the lower cover part 113 may include a ceramic material, for example, a barium titanate (BaTiO3)-based ceramic material.

[0055] On the other hand, the thickness tc of the covers 112 and 113 does not need to be particularly limited.

[0056] However, in order to more easily achieve miniaturization and high capacity of the multilayer electronic component, the thickness tc of the cover parts 112, 113 may be 100 μm or less, preferably 30 μm or less, and in the case of ultra-small products, more preferably 20 μm or less.

[0057] Here, the thickness tc of the cover parts 112, 113 may refer to the size of the cover parts 112, 113 in the first direction. In addition, the thickness tc of the cover parts 112, 113 may refer to the average thickness tc of the cover parts 112, 113, or may refer to the average size of the cover parts 112, 113 in the first direction.

[0058] The average size in the first direction of the cover parts 112 and 113 may be measured by scanning an image of a cross-section in the first and second directions of the body 110 with a scanning electron microscope (SEM) at a magnification of 10,000. More specifically, it may mean an average value calculated by measuring the size in the first direction at 30 points equally spaced in the second direction in an image obtained by scanning one cover part.

[0059] In addition, the average size in the first direction of the cover portion measured by the above-mentioned method may be substantially the same as the average size in the first direction of the cover portion in the cross-sections of the main body 110 in the first and third directions.

[0060] Meanwhile, the multilayer electronic component 100 may include side margin portions 114 and 115 disposed on both end surfaces of the body 110 in the third direction.

[0061] More specifically, the side margin portions 114, 115 may include a first side margin portion 114 disposed on the fifth surface 5 of the main body 110 and a second side margin portion 115 disposed on the sixth surface 6 of the main body 110.

[0062] As shown in the figure, the side margin portions 114, 115 may refer to the areas between the end surfaces in the third direction of the first and second internal electrodes 121, 122 and the boundary surface of the body 110, based on the cross-sections in the first and third directions of the body 110.

[0063] The side margin portions 114, 115 can be formed by applying a conductive paste to the ceramic green sheet applied to the capacitance forming portion Ac to form the internal electrodes 121, 122, except for the areas where the side margin portions 114, 115 are formed, and then cutting the laminated internal electrodes 121, 122 so that they are exposed on the fifth and sixth surfaces 5, 6 of the main body 110 in order to suppress steps caused by the internal electrodes 121, 122, and then stacking a single dielectric layer 111 or two or more dielectric layers 111 in the third direction on both end surfaces in the third direction of the capacitance forming portion Ac.

[0064] The side margins 114 and 115 essentially serve to prevent damage to the internal electrodes 121 and 122 due to physical or chemical stress.

[0065] The first side margin portion 114 and the second side margin portion 115 do not include the internal electrodes 121, 122, and may include the same material as the dielectric layer 111. That is, the first side margin portion 114 and the second side margin portion 115 may include a ceramic material, for example, a barium titanate (BaTiO3)-based ceramic material.

[0066] On the other hand, the width wm of the first and second side margin portions 114, 115 does not need to be particularly limited.

[0067] However, in order to more easily achieve miniaturization and high capacity of the multilayer electronic component 100, the width wm of the side margin portions 114, 115 may be 100 μm or less, preferably 30 μm or less, and in the case of ultra-small products, more preferably 20 μm or less.

[0068] Here, the width wm of the side margin portions 114, 115 may refer to the size of the side margin portions 114, 115 in the third direction. In addition, the width wm of the side margin portions 114, 115 may refer to the average width wm of the side margin portions 114, 115, or may refer to the average size of the side margin portions 114, 115 in the third direction.

[0069] The average size in the third direction of the side margin portions 114, 115 may be measured by scanning an image of a cross-section in the first and third directions of the body 110 with a scanning electron microscope (SEM) at a magnification of 10,000. More specifically, it may refer to an average value calculated by measuring the sizes in the third direction at 10 points equally spaced in the first direction in an image obtained by scanning one side margin portion.

[0070] In one embodiment of the present invention, a structure in which the ceramic electronic component 100 has two external electrodes 131, 132 is described, but the number and shapes of the external electrodes 131, 132 can be changed depending on the shape of the internal electrodes 121, 122 and other purposes.

[0071] The outer electrodes 131 and 132 may be disposed on the body 110 and connected to the inner electrodes 121 and 122 .

[0072] More specifically, the external electrodes 131, 132 may include first and second external electrodes 131, 132 disposed on the third and fourth surfaces 3, 4 of the body 110, respectively, and connected to the first and second internal electrodes 121, 122, respectively. That is, the first external electrode 131 may be disposed on the third surface 3 of the body and connected to the first internal electrode 121, and the second external electrode 132 may be disposed on the fourth surface 4 of the body and connected to the second internal electrode 122.

[0073] Furthermore, the external electrodes 131, 132 may be arranged to extend over a portion of the first and second surfaces 1, 2 of the body 110, or may be arranged to extend over a portion of the fifth and sixth surfaces 5, 6 of the body 110. That is, the first external electrode 131 may be arranged over a portion of the first, second, fifth and sixth surfaces 1, 2, 5 and 6 of the body 110 and over the third surface 3 of the body 110, and the second external electrode 132 may be arranged over a portion of the first, second, fifth and sixth surfaces 1, 2, 5 and 6 of the body 110 and over the third surface 3 of the body 110.

[0074] Specifically, the external electrodes 131 , 132 may include connection portions disposed on the third and fourth faces 3 , 4 , and band portions extending from the connection portions to portions of the first and second faces 1 , 2 .

[0075] The first external electrode 131 may include a first connection portion disposed on the third surface 3, a first band portion extending from the first connection portion to a portion of the first surface 1, and a third band portion extending from the first connection portion to a portion of the second surface 2. The second external electrode 132 may include a second connection portion disposed on the fourth surface 4, a second band portion extending from the second connection portion to a portion of the first surface 1, and a fourth band portion extending from the second connection portion to a portion of the second surface 2.

[0076] Referring to FIG. 3, in the present invention, a "connection portion" may refer to a portion of the external electrode that is arranged between an extension line EL1 of the first surface and an extension line EL2 of the second surface, and a "band portion" may refer to a portion of the external electrode that is arranged below the extension line EL1 of the first surface in the first direction and above the extension line EL2 of the second surface in the first direction.

[0077] Meanwhile, the external electrodes 131 and 132 may be formed using any material having electrical conductivity, such as a metal, and the specific material may be determined taking into consideration electrical characteristics, structural stability, etc., and may further have a multi-layer structure.

[0078] For example, the external electrodes 131 and 132 may include electrode layers 131a and 132a disposed in contact with the main body 110, and conductive resin layers 131c and 132c disposed on the electrode layers 131a and 132a. For example, the electrode layers 131a and 132a and the conductive resin layers 131c and 132c may be formed by transferring a sheet containing a conductive metal onto the main body, or by applying / dipping a paste.

[0079] More specifically, the electrode layers 131a, 132a may be fired electrodes containing a first conductive metal and glass, and the conductive resin layers 131c, 132c may be resin-based electrodes containing a second conductive metal and resin.

[0080] That is, the conductive metal contained in the first electrode layers 131a and 132a can be referred to as a first conductive metal, and the conductive metal contained in the conductive resin layers 131c and 132c can be referred to as a second conductive metal.

[0081] The conductive metal may include, but is not limited to, one or more selected from the group consisting of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof. That is, the type of conductive metal may be one or more.

[0082] More specifically, the electrode layers 131a, 132a contain glass, thereby serving to improve adhesion to the main body 110, and the conductive resin layers 131c, 132c contain resin, thereby serving to improve bending strength.

[0083] The first conductive metal used for the electrode layers 131a and 132a is not particularly limited as long as it can be electrically connected to the internal electrodes 121 and 122 to form capacitance, and may include, for example, at least one selected from the group consisting of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof. The first electrode layers 131a and 132a may be formed by applying a conductive paste prepared by adding glass frit to the conductive metal particles, and then firing the paste.

[0084] The second conductive metal included in the conductive resin layers 131c and 132c may serve to electrically connect the electrode layers 131a and 132a.

[0085] The second conductive metal contained in the conductive resin layers 131c, 132c is not particularly limited as long as it is a material that can be electrically connected to the electrode layers 131a, 132a, and may include one or more selected from the group consisting of nickel (Ni), copper (Cu), palladium (Pd), silver (Ag), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), and alloys thereof.

[0086] In this case, the first and second conductive metals may be the same, for example, the first and second conductive metals may be copper (Cu). However, the present invention is not limited thereto, and the first and second conductive metals may be different from each other. In addition, when there are a plurality of first and second conductive metals, the first and second conductive metals may include the same metal and different metals.

[0087] The second conductive metal contained in the conductive resin layers 131c and 132c may include one or more of flake particles and spherical particles. That is, the conductive metal may be composed of only flake particles or only spherical particles, or may be a mixture of flake particles and spherical particles. Here, the spherical particles may include a shape that is not completely spherical, for example, a shape in which the length ratio of the major axis to the minor axis (major axis / minor axis) is 1.45 or less. The flake particles refer to particles having a flat and elongated shape, and are not particularly limited, but may be, for example, a shape in which the length ratio of the major axis to the minor axis (major axis / minor axis) is 1.95 or more.

[0088] The lengths of the major and minor axes of the spherical and flaky particles can be measured from images obtained by scanning cross-sections in the first and second directions cut at the center of the ceramic electronic component in the third direction with a scanning electron microscope (SEM).

[0089] The resin contained in the conductive resin layers 131c and 132c may ensure bonding and absorb shock. The resin contained in the conductive resin layers 131c and 132c is not particularly limited as long as it has bonding and shock absorbing properties and can be mixed with conductive metal particles to form a paste, and may include, for example, an epoxy resin.

[0090] In addition, the conductive resin layers 131c and 132c may include a plurality of metal particles, an intermetallic compound, and a resin. By including the intermetallic compound, electrical connectivity with the electrode layers 131a and 132a may be improved. The intermetallic compound may function to connect the plurality of metal particles to improve electrical connectivity, and may function to surround the plurality of metal particles to connect them to each other.

[0091] At this time, the intermetallic compound may include a metal having a melting point lower than the curing temperature of the resin. That is, since the intermetallic compound includes a metal having a melting point lower than the curing temperature of the resin, the metal having a melting point lower than the curing temperature of the resin melts during the drying and curing process, and forms an intermetallic compound with a part of the metal particles to surround the metal particles. At this time, the intermetallic compound may include a low melting point metal of preferably 300° C. or less.

[0092] For example, it may contain Sn, which has a melting point of 213°C to 220°C. During the drying and hardening process, Sn melts, and the molten Sn wets high melting point metal particles such as Ag, Ni, or Cu by capillary action and reacts with some of the Ag, Ni, or Cu metal particles to form intermetallic compounds such as Ag3Sn, Ni3Sn4, Cu6Sn5, and Cu3Sn. Ag, Ni, or Cu that is not involved in the reaction remains in the form of metal particles.

[0093] Thus, the metal particles may include one or more of Ag, Ni, and Cu, and the intermetallic compound may include one or more of Ag3Sn, Ni3Sn4, Cu6Sn5, and Cu3Sn.

[0094] Meanwhile, multilayer ceramic capacitors can be used as components of various electronic devices due to the advantages of being small in size, having high capacitance, and being easy to mount. As various electronic devices such as computers and mobile devices become smaller and have higher output, there is an increasing demand for multilayer ceramic capacitors to be smaller and have higher capacitance.

[0095] However, when an external impact is applied to a ceramic body, the ceramic body has a tendency to break without undergoing plastic deformation, and therefore a structure capable of absorbing or eliminating the tensile stress transmitted to the ceramic body is required to prevent bending cracks.

[0096] Therefore, as mentioned above, a method is being used in which a resin-based electrode is added to the external electrode structure to suppress the transmission of external bending stress to the ceramic body, but research is being conducted on various structural designs and materials to further improve bending strength.

[0097] Therefore, the present invention applies a silver (Ag) coating layer structure to the band portion of the external electrode where bending stress is concentrated, thereby inducing peel-off in the external electrode structure and preventing the occurrence of bending cracks.

[0098] The external electrodes 131 and 132 according to an embodiment of the present invention may include silver (Ag) coating layers 131b and 132b disposed between the electrode layers 131a and 132a of the band portion and the conductive resin layers 131c and 132c.

[0099] In other words, the silver (Ag) coating layers 131b, 132b may be disposed in the band portion region of the external electrode. For example, referring to FIG. 3, the silver coating layers 131b, 132b may be disposed in a portion disposed below the extension line EL1 of the first surface in the first direction and above the extension line EL2 of the second surface in the first direction, more specifically, between the electrode layers 131a, 132a and the conductive resin layers 131c, 132c of the band portion, and may be disposed in a portion disposed below the extension line EL1 of the first surface in the first direction and above the extension line EL2 of the second surface in the first direction.

[0100] By disposing the silver (Ag) coating layers 131b, 132b between the electrode layers 131a, 132a and the conductive resin layers 131c, 132c of the band portion, peel-off is induced between the electrode layers 131a, 132a and the conductive resin layers 131c, 132c when bending stress is applied, thereby making it possible to further suppress the occurrence of bending cracks.

[0101] At this time, the average thickness of the silver (Ag) coating layers 131b and 132b may be 2 μm or more and 5 μm or less.

[0102] When the average thickness of the silver (Ag) coating layers 131b and 132b is in the range of 2 μm to 5 μm, peel-off due to bending stress can be more easily induced.

[0103] If the average thickness of the silver (Ag) coating layers 131b, 132b is less than 2 μm, peel-off may be partially induced, but bending cracks may occur. If the average thickness of the silver (Ag) coating layers 131b, 132b is more than 5 μm, the adhesive strength between the electrode layers 131a, 132a and the conductive resin layers 131c, 132c may decrease, resulting in a weakened adhesion strength.

[0104] The method of measuring the average thickness of the silver (Ag) coating layers 131b, 132b may be, for example, measuring the thickness at various points of the silver (Ag) coating layers 131b, 132b based on the cross-sections in the first and second directions of the laminated electronic component 100. More specifically, the linear size (thickness) in the first direction (perpendicular direction) from the electrode layers 131a, 132a may be measured at 10 points equally spaced in the second direction, and the average value of these may be taken as the average thickness of the silver (Ag) coating layers 131b, 132b. Alternatively, the average value may be taken as the size in the first direction at 10 points equally spaced in the second direction in the region of the silver (Ag) coating layers 131b, 132b substantially parallel to the first and second faces 1, 2 of the main body, and the average value of these may be taken as the average thickness of the silver (Ag) coating layers 131b, 132b.

[0105] According to an embodiment of the present invention, the silver (Ag) coating layers 131b, 132b may not be disposed between the electrode layers 131a, 132a and the conductive resin layers 131c, 132c of the connection portions.

[0106] If silver (Ag) coating layers 131b, 132b are further disposed at the connection portions, peel-off may be induced more easily, but the adhesive strength between the electrode layers 131a, 132a and the conductive resin layers 131c, 132c may decrease, and complete delamination may occur between the electrode layers 131a, 132a and the conductive resin layers 131c, 132c.

[0107] Meanwhile, the average atomic percentage of silver (Ag) in the silver (Ag) coating layers 131b and 132b may be 90 at% or more, preferably 95 at% or more. When expressed as an average mass percentage (wt%), the average mass percentage of silver (Ag) may be 95 wt% or more, preferably 97 wt% or more, more preferably 98 wt% or more, and there may be many points where 99 wt% or more is confirmed at each point.

[0108] The method for measuring the average atomic percentage (or average mass percentage) of silver (Ag) is not particularly limited, but for example, it may be an average value of atomic percentage values ​​of silver (Ag) measured at 10 points in the center of the silver (Ag) coating layers 131b and 132b when Energy Dispersive X-ray Spectroscopy (EDS) is performed on the 10 points based on the cross-sections in the first and second directions of the laminated electronic component 100. Alternatively, it may mean the atomic percentage value of silver (Ag) measured when EDS analysis of silver (Ag) is performed on the entire region of the silver (Ag) coating layers 131b and 132b.

[0109] In other words, the silver (Ag) coating layers 131b, 132b correspond to pure silver (Ag) containing little or no other conductive metals or alloys, and can be considered to be substantially pure silver (Ag).

[0110] The method of forming the silver (Ag) coating layer is not particularly limited, but may be, for example, the result of being formed by a galvanic replacement reaction.

[0111] More specifically, after the electrode layers 131a and 132a are baked, the electrode layers 131a and 132a are immersed in an aqueous silver (Ag) solution, for example, an aqueous silver nitrate (AgNO3) solution of 10 mM to 1 M (molarity, 1 M=1 mol / L) for 10 to 60 minutes to allow a silver (Ag) reduction reaction to occur, and then washed two to three times with distilled water to remove excess silver (Ag) reduction products or silver (Ag) ions, thereby forming a silver (Ag) coating layer of a substantially uniform thickness.

[0112] When immersing in a silver nitrate (AgNO3) aqueous solution, only the band portion of the electrode layer can be immersed to form a silver (Ag) coating layer, or the entire electrode layer can be immersed to form a silver (Ag) coating layer, and then the silver (Ag) coating layer formed on the connection portion can be removed and an (Ag) coating layer can be formed only on the electrode layer of the band portion, but this is not particularly limited.

[0113] Then, a paste containing a conductive metal and a resin may be applied or transferred onto the electrode layers 131a and 132a and the silver (Ag) coating layers 131b and 132b to form the conductive resin layers 131c and 132c.

[0114] Meanwhile, the length of the region where the silver (Ag) coating layer is formed according to an embodiment of the present invention may be 50% or more of the length of the electrode layer of the band portion.

[0115] The upper limit of the length of the silver (Ag) coating layer for inducing peel-off is not particularly limited, but due to the adhesion strength between the electrode layers 131a, 132a and the conductive resin layers 131c, 132c, the upper limit of the silver (Ag) coating layer may be 80% or less, preferably 70% or less.

[0116] In other words, the length of the region where the silver (Ag) coating layer is formed can be 50% or more of the length of the boundary region between the electrode layer of the band portion and the conductive resin layer. More specifically, when the length of the electrode layers 131a, 132a of the band portion is IFL and the length of the silver (Ag) coating layers 131b, 132b is L, 50%≦L / IFL or L / IFL≦80% can be satisfied.

[0117] For example, referring to FIG. 5, the length IFL of the electrode layers 131a, 132a of the band portion may mean the sum (L+L') of the interface length L between the electrode layers 131a, 132a of the band portion and the silver (Ag) coating layers 131b, 132b and the interface length L' (not shown) between the electrode layers 131a, 132a of the band portion and the conductive resin layers 131c, 132c of the band portion, and the length L of the silver (Ag) coating layers 131b, 132b may mean the interface length L between the electrode layers 131a, 132a of the band portion and the silver (Ag) coating layers 131b, 132b.

[0118] When the ratio L / IFL of the length L of the silver (Ag) coating layers 131b, 132b to the length IFL of the electrode layers 131a, 132a of the band portion satisfies 50%≦L / IFL or L / IFL≦80%, peel-off due to bending stress can be induced more easily. On the other hand, when the L / IFL value is compared between 70% and 80%, there may be almost no difference in the peel-off effect due to bending stress.

[0119] When the ratio L / IFL of the length L of the silver (Ag) coating layers 131b and 132b to the length IFL of the electrode layers 131a and 132a in the band portion is less than 50% (L / IFL < 50%), peel-off may be partially induced, but there is a risk of bending cracks occurring. When the ratio L / IFL of the length L of the silver (Ag) coating layers 131b and 132b to the length IFL of the electrode layers 131a and 132a in the band portion exceeds 80% (80% < L / IFL), the adhesive force between the electrode layers 131a and 132a and the conductive resin layers 131c and 132c may decrease, and the fixing strength may become weak.

[0120] The method for measuring the length IFL of the electrode layer and the length L of the silver (Ag) coating layer in the band portion is not particularly limited. For example, based on the cross-sections in the first and second directions of the laminated electronic component, after imaging the band portion region of the external electrode where the silver (Ag) coating layer is located through a scanning electron microscope (SEM) at a magnification of 2000, it can be measured using the freehand line function of the Image J program. More specifically, the length L of the interface between the electrode layer and the silver (Ag) coating layer in the band portion, which is the section to be measured by selecting the freehand line function, can be measured, the length of the interface between the electrode layer in the band portion and the conductive resin layer in the band portion can be measured, and the length IFL of the electrode layer in the band portion, which is the sum of L and L', can be obtained.

[0121] As a more specific example of a method for measuring the content of elements contained in the silver (Ag) coating layers 131b and 132b, in the case of a destructive method, the components inside the dielectric crystal grains at the center of the chip can be analyzed using SEM-EDS, TEM-EDS, or STEM-EDS. First, an analysis sample is prepared by cutting a region including a dielectric microstructure in a cross section of a body where sintering is completed, using a focused ion beam (FIB) device. Then, the surface damage layer of the cut sample is removed using argon (Ar) ion milling, and then each component is mapped from an image obtained using SEM-EDS, TEM-EDS, or STEM-EDS to perform qualitative / quantitative analysis. In this case, the qualitative / quantitative analysis graph of each component can be converted into mass percentage (wt%), atomic percentage (at%), or molar percentage (mol%) of each element.

[0122] As yet another method, the chip can be crushed to select the area containing the dielectric microstructure, and the components of the area containing the dielectric microstructure can be analyzed using an inductively coupled plasma optical emission spectrometer (ICP-OES), an inductively coupled plasma mass spectrometer (ICP-MS), or the like.

[0123] The plating layers 131d, 132d, 131e, and 132e can serve to improve mounting characteristics.

[0124] The types of plating layers 131d, 132d, 131e, and 132e are not particularly limited, and may be single-layer plating layers 131d, 132d containing one or more of nickel (Ni), tin (Sn), palladium (Pd), and alloys thereof, or may be formed of multiple plating layers 131d, 132d, 131e, and 132e.

[0125] As a more specific example of the plating layers 131d, 132d, 131e, and 132e, the plating layers 131d, 132d, 131e, and 132e may be Ni plating layers or Sn plating layers, or may be in a form in which a Ni plating layer and a Sn plating layer are sequentially formed on the conductive resin layers 131c and 132c, or in a form in which a Sn plating layer, a Ni plating layer, and a Sn plating layer are sequentially formed. Also, the plating layers 131d, 132d, 131e, and 132e may include a plurality of Ni plating layers and / or a plurality of Sn plating layers.

[0126] The size of the multilayer electronic component 100 does not need to be particularly limited.

[0127] However, in order to simultaneously achieve miniaturization and high capacity, the thickness of the dielectric layers and internal electrodes must be reduced and the number of layers must be increased, and in order to improve the dielectric breakdown voltage (BDV) characteristics under high voltage, the thickness of the dielectric layers and internal electrodes must be guaranteed to be constant. When all characteristics such as mechanical strength due to bending stress are taken into consideration, the effects of the present invention may be more pronounced in a multilayer electronic component 100 having a size of 3216 (length x width: 3.2 mm x 1.6 mm) or less.

[0128] The present invention will be described in more detail below with reference to examples. However, these examples are intended to aid in the specific understanding of the present invention, and the scope of the present invention is not limited to these examples.

[0129] (Example) Test Examples 1 to 10 were fabricated by the following method. After applying copper (Cu) paste on the ceramic body and firing it to form an electrode layer, it was immersed in an aqueous solution of 0.1 mM to 0.1 M silver nitrate (AgNO3) for 10 to 60 minutes so that a silver (Ag) reduction reaction occurs, and then washed with distilled water to remove excess silver (Ag) reduction products that had been removed from the surface, forming a silver (Ag) coating layer on the ceramic body and the electrode layer. Then, the silver (Ag) coating layer formed on the end-surface of the first and third surfaces of the electrode layer was mounted on a carrier plate and removed using adhesive tape. Then, a copper (Cu)-epoxy paste was applied on the electrode layer and the silver (Ag) coating layer and fired to form a conductive resin layer. Then, a nickel (Ni) plating layer and a tin (Sn) plating layer were formed on the conductive resin layer to complete a chip. The silver (Ag) coating layer was formed with various thicknesses and lengths depending on the molar concentration (M) of the silver nitrate (AgNO3) aqueous solution and the immersion time.

[0130] In Test Example 1, a chip was fabricated in the same manner as described above, except that it was immersed in a 0.1M aqueous solution of silver nitrate (AgNO3) for 30 minutes to generate a silver (Ag) reduction reaction, then washed with distilled water to remove excess silver (Ag) reduction products that had been detached from the surface, and a silver (Ag) coating layer was formed on the ceramic body and electrode layer. At this time, the average thickness of the silver (Ag) coating layer of the band portion was 3.4 μm, and the length L of the silver (Ag) coating layer relative to the length IFL of the electrode layer of the band portion was about 82%.

[0131] 6 and 7, which are images of scanning electron microscope (SEM) and EDS analysis for Example 1 of the present invention, a bending stress of 10 mm was applied to a chip to perform a severe limit evaluation beyond the guaranteed level for bending strength testing, and then, when the region between the electrode layer and the conductive resin layer of the band was observed with a scanning electron microscope (SEM) at a magnification of 2000, it was confirmed that peel-off occurred. When SEM-EDS analysis was performed on the region of the band, indicated by the dashed line in FIG. 6, where copper (Cu), silver (Ag), nickel (Ni) and tin (Sn) were detected, it was confirmed that peel-off occurred along the silver (Ag) coating layer between the electrode layer and the conductive resin layer of the band.

[0132] Next, Table 1 shows the evaluation results of bending crack, peel-off, and adhesion strength according to the average thickness of the silver (Ag) coating layer for each test example.

[0133] Test Example 2 is a test example in which an electrode layer is formed on a ceramic body, a conductive resin layer is formed on the electrode layer, and a silver (Ag) coating layer is not formed. A chip was manufactured in the same manner as Test Example 1, except for the process of forming the silver (Ag) coating layer.

[0134] Test Examples 3 to 5 were produced in the same manner as Example 1, except that the average thickness of the silver (Ag) coating layer was varied by varying the time of immersion in silver nitrate (AgNO3). More specifically, the average thickness of the silver (Ag) coating layer in each chip in Test Example 3 was less than 2 μm, the average thickness of the silver (Ag) coating layer in each chip in Test Example 4 was 2 μm or more and 5 μm or less, and the average thickness of the silver (Ag) coating layer in each chip in Test Example 5 was more than 5 μm.

[0135] The bending strength was evaluated by preparing 20 chips for each test example, mounting the 20 chips on a bending strength (piezo method) board (1.6T according to the AEC-Q200 evaluation rules) and conducting a limit evaluation beyond the guaranteed range. All 20 chips were then removed from the board and the cross-sections of each chip in the first and second directions were checked to count the number of chips that had bending cracks and peel-off.

[0136] Here, the bending strength (piezo method) can be evaluated as follows. First, five sample chips are mounted on a piezo PCB, and a DC bias is applied to the chips to create a potential difference and then bending is applied to express the piezoelectric properties. A potential difference is generated by the external force caused by bending, and the minute current generated by the change in potential difference can be measured and expressed in a graph; the graph thus generated is called a piezo graph, and this piezo graph is analyzed to analyze and evaluate the presence and location of defects.

[0137] The adhesion strength was evaluated according to the AEC-Q200 standard by applying a stress of 18N to the end surfaces of the chip in the first and second directions for 60 seconds. If a capacitance change of 10% or more occurred or the chip was detached, it was determined to be defective, and the number of defective chips was counted and reflected in Table 1.

[0138] After the evaluation of bending strength and adhesion strength, if even one chip was defective during the evaluation of adhesion strength, it was judged as "X". Even if there were no chips with adhesion strength defects, if any of the 20 chips had bending cracks or no peel-off occurred in any of the 20 chips, it was judged as "△". If all of the 20 chips had peel-off without adhesion strength defects or bending cracks, it was judged as "O".

[0139] [Table 1]

[0140] In Test Example 2, because no silver (Ag) coating layer was formed, bending cracks occurred in 5 out of 20 chips due to bending stress, peel-off occurred in 5 chips, and no chips had poor adhesion strength. This is because in Test Example 2, which is the case of a conventional chip in which no silver (Ag) coating layer was formed, although the adhesion strength between the electrode layer and the conductive resin layer was good, peel-off did not occur, and therefore bending cracks were determined to have occurred.

[0141] In test example 3, the average thickness of the silver (Ag) coating layer was formed to be less than 2 μm, so bending stress caused bending cracks in 3 out of 20 chips, peel-off in 10 chips, and no chips with poor adhesion strength. This is because bending cracks occurred in chips that did not experience peel-off, which indicates that the silver (Ag) coating layer was not formed properly.

[0142] In Test Example 4, the average thickness of the silver (Ag) coating layer was formed to be 2 μm or more and 5 μm or less, so among the 20 chips, none of them had bending cracks or poor adhesion strength due to bending stress, and 20 chips had peel-off. This is because the silver (Ag) coating layer was properly formed, and it is judged that the evaluations of bending cracks, peel-off, and adhesion strength all showed excellent results.

[0143] In Test Example 5, the average thickness of the silver (Ag) coating layer was formed to be more than 5 μm, so among the 20 chips, none of them had bending cracks due to bending stress, and among the 20 chips, peel-off occurred, but only two chips had poor adhesion strength. This is considered to be due to the excessive formation of the silver (Ag) coating layer, which weakened the adhesion between the electrode layer and the conductive resin layer.

[0144] Next, Table 2 shows the results of evaluating bending cracks, peel-off, and adhesion strength for each test example by changing the ratio L / IFL, which is the length L of the silver (Ag) coating layer to the length IFL of the electrode layer of the band part.

[0145] Test Example 6 is a test example in which an electrode layer is formed on a ceramic body, a conductive resin layer is formed on the electrode layer, and a silver (Ag) coating layer is not formed. A chip was produced in the same manner as Test Example 1, except for the process of forming the silver (Ag) coating layer.

[0146] Test Examples 7 to 10 were produced in the same manner as in Example 1, except that the lengths of the silver (Ag) coating layers were varied by varying the time of immersion in silver nitrate (AgNO3). More specifically, the L / IFL of the silver (Ag) coating layer in each chip in Test Example 7 was about 30% (±5% error), the L / IFL of the silver (Ag) coating layer in each chip in Test Example 8 was about 50% (±5% error), the L / IFL of the silver (Ag) coating layer in each chip in Test Example 9 was about 70% (±5% error), and the L / IFL of the silver (Ag) coating layer in each chip in Test Example 10 was more than 85%.

[0147] The bending strength and adhesion strength were evaluated in the same manner as in Table 1.

[0148] After the evaluation of bending strength and adhesion strength, if even one chip was defective during the evaluation of adhesion strength, it was judged as "X". If there were no chips that were defective in adhesion strength, but any chip out of 20 chips had bending cracks or no peel-off occurred in any of the 20 chips, it was judged as "△". If no adhesion strength or bending cracks occurred in any of the 20 chips but peel-off occurred, it was judged as "O".

[0149] [Table 2]

[0150] In Test Example 6, since no silver (Ag) coating layer was formed, bending cracks occurred in 5 out of 20 chips due to bending stress, peel-off occurred in 5 chips, and no chips had poor adhesion strength. This is because in Test Example 6, which is the case of a conventional chip without a silver (Ag) coating layer, although the adhesion strength between the electrode layer and the conductive resin layer was good, peel-off did not occur, and therefore bending cracks were determined to have occurred.

[0151] In test example 7, the chip L / IFL was formed at about 30% (±5% error), so bending stress caused bending cracks in 3 out of 20 chips, peel-off in 15 chips, and no chips with poor adhesion strength. This is because bending cracks occurred in chips that did not experience peel-off, which indicates that the silver (Ag) coating layer was not formed properly.

[0152] In test example 8, the L / IFL of the chip was formed at about 50% (±5% error), so among the 20 chips, none of them had bending cracks or poor adhesion strength due to bending stress, and 20 chips had peel-off. This is because the silver (Ag) coating layer was properly formed, and it is judged that the evaluations of bending cracks, peel-off, and adhesion strength all showed excellent results.

[0153] In test example 9, the L / IFL of the chip was formed at about 70% (±5% error), so none of the 20 chips had bending cracks or poor adhesion due to bending stress, and peel-off occurred in all 20 chips. This is because the silver (Ag) coating layer was properly formed, and it is judged that the evaluations of bending cracks, peel-off, and adhesion strength all showed excellent results.

[0154] In Test Example 10, the L / IFL of the chip was formed at over 85%, so none of the 20 chips had bending cracks due to bending stress, and peel-off occurred in the 20 chips, but only 2 chips had poor adhesion strength. This is believed to be due to the excessive formation of the silver (Ag) coating layer, which weakened the adhesion between the electrode layer and the conductive resin layer.

[0155] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above-described embodiment and the accompanying drawings, but is limited by the scope of the accompanying claims. Therefore, various substitutions, modifications and changes can be made by a person having ordinary knowledge in the art within the scope of the technical idea of ​​the present invention described in the claims, and these also belong to the scope of the present invention.

[0156] In addition, the expression "one embodiment" used in the present invention does not mean the same embodiment, but is provided to emphasize and describe each unique feature that is different from the others. However, the above-mentioned one embodiment does not exclude being realized in combination with the features of another embodiment. For example, even if a matter described in a specific embodiment is not described in another embodiment, it can be understood as a description related to the other embodiment, unless there is a description that is opposite or contradictory to the matter in the other embodiment.

[0157] The terms used in the present invention are merely used to describe one embodiment and are not intended to limit the present invention. In this case, a singular expression includes a plural expression unless the context clearly indicates otherwise. [Explanation of symbols]

[0158] 100: Multilayer electronic components 110: Main unit 111: Dielectric layer 112, 113: Cover part 114, 115: Side margin 121, 122: Internal electrode 131, 132: External electrode 131a, 132a: Electrode layer 131b, 132b: silver (Ag) coating layer 131c, 132c: Conductive resin layer 131d, 132d: first plating layer 131e, 132e: second plating layer

Claims

1. a body including dielectric layers and internal electrodes alternately disposed with the dielectric layers in a first direction, the body including first and second surfaces facing each other in the first direction, third and fourth surfaces connected to the first and second surfaces and facing each other in the second direction, and fifth and sixth surfaces connected to the first to fourth surfaces and facing each other in the third direction; an external electrode including a connection portion disposed on the third and fourth surfaces and a band portion extending from the connection portion to a portion of the first and second surfaces; the external electrode includes an electrode layer connected to the internal electrode and including a first conductive metal and glass, a conductive resin layer disposed on the electrode layer and including a second conductive metal and resin, and a silver (Ag) coating layer disposed between the electrode layer of the band portion and the conductive resin layer, The average thickness of the silver (Ag) coating layer is 2 μm or more and 5 μm or less.

2. 2. The multilayer electronic component according to claim 1, wherein the silver (Ag) coating layer is not disposed between the electrode layer and the conductive resin layer of the connection portion.

3. 2. The multilayer electronic component according to claim 1, wherein the silver (Ag) coating layer has an average atomic percentage of silver (Ag) of 90 at % or more.

4. 2. The multilayer electronic component according to claim 1, wherein the silver (Ag) coating layer has an average mass percentage of silver (Ag) of 95 wt % or more.

5. 2. The multilayer electronic component according to claim 1, wherein when the length of the electrode layer of the band portion is IFL and the length of the silver (Ag) coating layer is L, 50%≦L / IFL is satisfied.

6. The multilayer electronic component according to claim 5 , wherein L / IFL≦80% is satisfied.

7. 2. The multilayer electronic component according to claim 1, wherein the first and second conductive metals are the same metal.

8. 8. The multilayer electronic component according to claim 7, wherein the first and second conductive metals are copper (Cu).

9. The multilayer electronic component according to claim 1 , wherein the external electrodes further include a plating layer disposed on the conductive resin layer.

10. a body including dielectric layers and internal electrodes alternately disposed with the dielectric layers in a first direction, the body including first and second surfaces facing each other in the first direction, third and fourth surfaces connected to the first and second surfaces and facing each other in the second direction, and fifth and sixth surfaces connected to the first to fourth surfaces and facing each other in the third direction; an external electrode including a connection portion disposed on the third and fourth surfaces and a band portion extending from the connection portion to a portion of the first and second surfaces; the external electrode includes an electrode layer connected to the internal electrode and including a first conductive metal and glass, a conductive resin layer disposed on the electrode layer and including a second conductive metal and resin, and a silver (Ag) coating layer disposed between the electrode layer of the band portion and the conductive resin layer, The silver (Ag) coating layer has an average atomic percentage of silver (Ag) of 90 at % or more.

11. The multilayer electronic component according to claim 10 , wherein the silver (Ag) coating layer is not disposed between the electrode layer and the conductive resin layer of the connection portion.

12. 11. The multilayer electronic component according to claim 10, wherein 50%≦L / IFL is satisfied, where IFL is a length of the electrode layer of the band portion, and L is a length of the silver (Ag) coating layer.

13. The multilayer electronic component according to claim 12 , wherein L / IFL≦80% is satisfied.

14. 11. The multilayer electronic component according to claim 10, wherein the first and second conductive metals are the same metal.

15. The multilayer electronic component according to claim 14 , wherein the first and second conductive metals are copper (Cu).

16. The multilayer electronic component according to claim 10 , wherein the external electrodes further include a plating layer disposed on the conductive resin layer.

Citation Information

Patent Citations

  • Multilayer ceramic capacitor

    JP2018098475A

  • Multi-layer ceramic electronic component

    KR1020190116177A